2016
DOI: 10.7763/ijiet.2016.v6.747
|View full text |Cite
|
Sign up to set email alerts
|

Web Developer Knowledge and Skills 2014

Abstract: Abstract-The authors collected data regarding the current demand for web developers, the education level requested, and the specific skills requested over a number of months on Dice.com. The requested skills were tabulated, categorized, and totals for both the categories and individual skills were computed. The key categories and specific skills are enumerated and the results show that the web development field requires an incredibly diverse set of knowledge and skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These data sets showed that 25% of web developers are independent and self-taught. Photoshop and JavaScript libraries are necessary [6]. Table I, summarized the study finding.…”
Section: A Us It Job Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…These data sets showed that 25% of web developers are independent and self-taught. Photoshop and JavaScript libraries are necessary [6]. Table I, summarized the study finding.…”
Section: A Us It Job Surveymentioning
confidence: 99%
“…Client-side scripting was the most needed or requested talent (85.4% asked for one or more scripting languages). More than 50% of the advertising required one or more of the following skills: server-side scripting (61.7%), JavaScript libraries (60.5%), programming languages (55.5%), and database technologies (52.3%) [6].…”
Section: A Us It Job Surveymentioning
confidence: 99%
See 1 more Smart Citation